2020
DOI: 10.1002/jlb.3mir0320-272r
|View full text |Cite
|
Sign up to set email alerts
|

Itch regulation of innate and adaptive immune responses in mice and humans

Abstract: The E3 ubiquitin ligase Itch has long been appreciated to be a critical suppressor of inflammation, first identified as a regulator of Th2 differentiation and lung inflammation. Recent studies have revealed novel roles for this protein in mouse and human disease, and it is now clear that Itch also limits the function of other lymphocytes, innate immune cells, and nonhematopoietic cells to regulate immunity. In addition to Th2 cells, Itch also regulates Th17 and regulatory T cells. Itch regulates humoral immuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 84 publications
1
4
0
Order By: Relevance
“…ITCH is an E3 ubiquitination ligase can mediate the ubiquitination of downstream targets and then regulate immune responses. 23 In the present study, by using Co-IP assay, we found that ITCH directly bound to LKB1 (Figure 4A). In addition, ITCH overexpression reduced LKB1 levels in macrophages, with this effect being abrogated by treatment with MG132, a proteasome inhibitor (Figure 4B).…”
Section: Role Of Lkb1 In the Effects Of Itch On Macrophage Ldl Uptake...supporting
confidence: 59%
“…ITCH is an E3 ubiquitination ligase can mediate the ubiquitination of downstream targets and then regulate immune responses. 23 In the present study, by using Co-IP assay, we found that ITCH directly bound to LKB1 (Figure 4A). In addition, ITCH overexpression reduced LKB1 levels in macrophages, with this effect being abrogated by treatment with MG132, a proteasome inhibitor (Figure 4B).…”
Section: Role Of Lkb1 In the Effects Of Itch On Macrophage Ldl Uptake...supporting
confidence: 59%
“…Given the inflammatory component triggered by ITCH [ 39 ], we assessed whether the ITCH -induced steatohepatitis phenotype is a consequence of the ITCH -induced inflammatory phenotype in immune cells, thus proceeding to BMT between WT and ITCH −/− mice fed a short-term MCD ( Figure S9A ). We observed a gradual increase in steatohepatitis score by comparing WT→WT, ITCH −/− →WT, WT→ ITCH −/− , and ITCH −/− →I TCH −/− ( Figure S9B ), which suggests that ITCH expression in both hepatic and myeloid cells plays a role in the NASH phenotype ( Figure S9 , Table S10 ).…”
Section: Resultsmentioning
confidence: 99%
“…We used mouse models to confirm the link between ITCH and BCAA degradation found in human analysis; however, mice models do not perfectly match human NAFLD. In particular, the whole-body ITCH knockout has different phenotypes, due to pleiotropic effects of ITCH on inflammation and autoimmunity, that may imply actions on different targets [ 39 ]. From our human and mouse models, we observed the loss of ITCH expression in both hepatocyte and non-hepatocyte compartments, but whether one or both is more relevant in the context of NAFLD remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…We found that some mutation cell associations identified by the method have been reported in the literature. For example, it has been proposed that deficiency of E3 ubiquitin ligase (ITCH) altered CD4 T-cell and B-cell responses in mice and humans ( Field et al, 2020 ); HIVEP2 was found to play a crucial role in the control of Th2 cell differentiation by regulating NF-κB function, whose ortholog gene HIVEP3 may substitute for the function of HIVEP2 ( Kimura et al, 2005 ). This indicates that the SMDIC method could identify mutation-specific cells in different cancers.…”
Section: Resultsmentioning
confidence: 99%